Implications of Transaction Costs for the Post–Earnings Announcement Drift - NG, JEFFREY; RUSTICUS, TJOMME O.; VERDI, RODRIGO S. (Journal of Accounting Research, 2008)
ABSTRACT This paper examines the effect of transaction costs on the post–earnings announcement drift (PEAD). Using standard market microstructure features we show that transaction costs constrain the informed trades that are necessary to incorporate earnings information into price. This implies weaker return responses at the time of the earnings announcement and higher subsequent returns drift for firms with higher transaction costs. Consistent with this prediction, we find that earnings response coefficients are lower for firms with higher transaction costs. Using portfolio analyses, we find that the profits of implementing the PEAD trading strategy are significantly reduced by transaction costs. In addition, we show, using a combination of portfolio and regression analyses, that firms with higher transaction costs are the ones that provide the higher abnormal returns for the PEAD strategy. Our results indicate that transaction costs can provide an explanation not only for the persistence but also for the existence of PEAD.